2019
DOI: 10.1371/journal.pone.0225716
|View full text |Cite
|
Sign up to set email alerts
|

Clinical risk assessment in early pregnancy for preeclampsia in nulliparous women: A population based cohort study

Abstract: ObjectiveTo evaluate the capacity of multivariable prediction of preeclampsia during pregnancy, based on detailed routinely collected early pregnancy data in nulliparous women.Design and settingA population-based cohort study of 62 562 pregnancies of nulliparous women with deliveries 2008–13 in the Stockholm-Gotland Counties in Sweden.MethodsMaternal social, reproductive and medical history and medical examinations (including mean arterial pressure, proteinuria, hemoglobin and capillary glucose levels) routine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 41 publications
0
28
0
5
Order By: Relevance
“…The characteristics of study populations showed that pregnant women and fetuses or newborns were the populations of most studies developed using LR and non-LR models, respectively. Among pregnant women, the LR algorithm was mostly applied to develop predictions for outcome categories of obstetric labor (13/77, 17%) [36,46,47,54,57,62,64,70,83,86,91,97,103], pregnancy-induced hypertension (12/77, 16%) [30,31,43,48,55,65,66,68,76,81,93,105], and gestational diabetes (7/77, 9%) [33,45,49,84,94,100,104]. Among fetus or newborn populations, non-LR algorithms were mostly applied to develop predictions for outcome categories of premature birth (12/50, 24%) [111,112,115,116,118,119,121,122,125,130,141,143] and fetal distress (9/50, 18%) [113,…”
Section: Lr and Other Machine Learning Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of study populations showed that pregnant women and fetuses or newborns were the populations of most studies developed using LR and non-LR models, respectively. Among pregnant women, the LR algorithm was mostly applied to develop predictions for outcome categories of obstetric labor (13/77, 17%) [36,46,47,54,57,62,64,70,83,86,91,97,103], pregnancy-induced hypertension (12/77, 16%) [30,31,43,48,55,65,66,68,76,81,93,105], and gestational diabetes (7/77, 9%) [33,45,49,84,94,100,104]. Among fetus or newborn populations, non-LR algorithms were mostly applied to develop predictions for outcome categories of premature birth (12/50, 24%) [111,112,115,116,118,119,121,122,125,130,141,143] and fetal distress (9/50, 18%) [113,…”
Section: Lr and Other Machine Learning Algorithmsmentioning
confidence: 99%
“…The same algorithm was applied to a prediction model from a non-LR low ROB study in pre-eclampsia [147]. For random effects modeling, this model also significantly outperformed those from 4 LR studies (1.2, 95% CI 0.72-1.67) [31,48,65,76].…”
Section: Comparison Of the Predictive Performancementioning
confidence: 99%
“…In this analysis, maternal age and primiparity were selected for the primary predictive model and therefore were not assessed separately. Of course, the choice of these two features for the basic predictive model was dictated by the results found in the literature, as both are known risk factors for hypertension in pregnancy [9,20,51,52].…”
Section: Discussionmentioning
confidence: 99%
“…However, despite significant advances in understanding many of the molecular processes involved in the pathogenesis of preeclampsia, a reliable method of predicting hypertension in pregnancy remains yet to be developed. Maternal risk factors are still an important element in risk identification [ 13 , 15 , 20 ]. In many studies, a higher risk of preeclampsia (PE) and/or GH has been associated with pre-pregnancy obesity (body mass index, BMI ≥ 30 kg/m 2 ), comorbidities (such as chronic hypertension), older maternal age, primiparity, diagnosis of PE in a previous pregnancy, as well as with PE in the mother or a sister, and short or long gaps between pregnancies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation